Validación del método analítico por espectrofotometría uv/vis para la cuantificación de sildenafilo 50mg tabletas masticables” - Saldaña Calderón, Luis Alberto (2011)
In the present essay the spectrophotometric analytic method to quantify Sildenafilo chewable tablets was validated. To analyze Sildenafilo chewable tablets (50 mg, allotment N° 0129328 from Laboratorios Induquimica S.A.), a mixture of water:methanol (40:60) was used as dissolvent and a maximum absorbance wavelength of 232 nm. The method used in this essay was specific to the analyte between the excipients. The samples were exposed to acid, alkaline degradation, photolysis, oxidation, thermolysis, and relative humidity; reaching a minor interference of 2.0%. The linear test for the method showed a correlation coefficient of 0.99957; the linear statistical test and response factor, expressed conformity and the linearity the system showed a correlation factor of 0.997828. The accuracy of the method as percentage of recovery was 98.199%, the G of Cochran test was bellow charts (0.400 < 0,871) and the t Student test was below charts (2,033 < 2,306), which expressed completeness according to specifications. The system repeatability was support with a CV of 0.832%, and the repeatability of the method was supported by a CV of 0.698%. The intermediate precision between one analyzer and other got a CV of 1.812%. The reproducibility between Laboratorios Induquimica S.A. and Laboratorios Farmaceúticos Markos S.A. got a CV of 1.784%; the results were acceptable to validate the procedure. The validation parameters determined allowed validating the analytic method proposed to quantify Sildenafilo chewable tablets by Laboratorios Indquimica S.A